2022
DOI: 10.1039/d1ra08111j
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-catalyzed acylation of levoglucosan in continuous flow: antibacterial and biosurfactant studies

Abstract: Ipase-catalyzed transesterification of LG under continuous flow conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…These antibacterial activities may be due to the presence of several compounds which have antimicrobial activity. These compounds include 2-furancarboxaldehyde; 5-(hydroxymethyl)- [28]; 1,6-anhydro-β-D-glucopyranose [29]; hexadecanoic acid; methyl ester; 9-octadecenoic acid; methyl ester [52]; heptadecanoic acid; 16-methyl ester [35]; phthalic acid; bis(7-methyloctyl) ester [41]; hordenine [61]; fraxetin [62]; piperine [63]; stearamide [64]; and erucamide [65]. Wahab et al reported the antibacterial activity against some Gram-positive and Gram-negative bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…These antibacterial activities may be due to the presence of several compounds which have antimicrobial activity. These compounds include 2-furancarboxaldehyde; 5-(hydroxymethyl)- [28]; 1,6-anhydro-β-D-glucopyranose [29]; hexadecanoic acid; methyl ester; 9-octadecenoic acid; methyl ester [52]; heptadecanoic acid; 16-methyl ester [35]; phthalic acid; bis(7-methyloctyl) ester [41]; hordenine [61]; fraxetin [62]; piperine [63]; stearamide [64]; and erucamide [65]. Wahab et al reported the antibacterial activity against some Gram-positive and Gram-negative bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanidin glycoside from trueno fruits ( Ligustrum japonicum ) was subjected to transesterification with vinyl cinnamate and cyanidin-3- O -(4‴-cinnamoyl)rutinoside ( Figure 2 e) and was synthesized at a 45.5% conversion yield [ 14 ]. The usage of vinyl esters in the enzymatic reactions is a well-known way to increase the conversion yield due to the shifting of the equilibrium state towards the formation of the product because of the tautomerization of vinyl alcohol to acetaldehyde [ 22 ].…”
Section: Lipophilization Of Extracts From Fruitsmentioning
confidence: 99%
“…As extensively described in the literature, the spatial arrangement of the hydroxyl groups and consequent stabilization by intramolecular hydrogen bonds (Scheme ) hinder chemical and enzymatic transformations of LGA, leading to time-consuming reactions. , Enzymatically, the high polarity of LGA is also a disadvantage, restricting the scope of solvents suitable for use to a handful of polar solvents, which in general inhibit enzyme activity . Our research group has recently reported the high regioselectivity of Novozym 435 (N435, Candida antarctica lipase B immobilized on acrylic resin) toward C2 and C4 hydroxyl moieties during acetylation using long-chain aliphatic esters, while other lipases showed an increased preference for the OH at C4 at higher temperatures. , These findings have led to the possibility of synthesizing LGA-based linear polymers, possessing the rigid structure from LGA with pending hydroxyl moieties available for post-polymerization modifications.…”
Section: Introductionmentioning
confidence: 98%
“…In this context, levoglucosan (1,6-anhydro-β- d -glucopyranose; LGA) has been identified as an attractive chemical platform. LGA is an anhydrous sugar obtained from the fast pyrolysis of cellulosethe major component of lignocellulosic biomass and has a rigid structure, with three hydroxyl groups disposed in trans -positions on a pyranose ring. It was already subjected to different reactions to produce diverse high-added value products, such as levoglucosenone, 5-hydroxymethylfurfural, furfural, glucose-6-phosphate, gluconic acid, sorbitol, and it was even tested for the production of biosurfactants and in antibacterial assays. …”
Section: Introductionmentioning
confidence: 99%